Parkinson’s Disease, Cortical Dysfunction, and Alpha-Synuclein - Caviness, John N. (2011)
BACKGROUND: The ability to understand how Parkinson’s disease (PD) neurodegeneration leads to cortical dysfunction will be critical for developing therapeutic advances in PD dementia (PD-D). The overall purpose of this project was to study the small amplitude cortical myoclonus in PD as an in vivo model of focal cortical dysfunction secondary to PD neurodegeneration. The objectives were to test the hypothesis that cortical myoclonus in PD is linked to abnormal levels of α-synuclein in primary motor cortex and to define its relationship to various biochemical, clinical, and pathological measures. METHODS: Primary motor cortex was evaluated for 11 PD subjects with (PD+Myoclonus group) and 8 without (PD group) electrophysiologically confirmed cortical myoclonus who had premortem movement and cognitive testing. Similarly assessed 9 controls were used for comparison. Measurements for α-synuclein, Aβ-42 peptide, and other biochemical measures were made in primary motor cortex. RESULTS: A 36% increase in α-synuclein was found in the motor cortex of PD+Myoclonus cases when compared to PD without myoclonus. This occurred without significant differences in insoluble α-synuclein, phosphorylated to total α-synuclein ratio, or Aβ-42 peptide levels. Higher total motor cortex α-synuclein levels significantly correlated with the presence of cortical myoclonus but did not correlate with multiple clinical or pathological findings. CONCLUSIONS: These results suggest an association between elevated α-synuclein and the dysfunctional physiology arising from the motor cortex in PD+Myoclonus cases. Alzheimer’s disease pathology was not associated with cortical myoclonus in PD. Cortical myoclonus arising from motor cortex is a model to study cortical dysfunction in PD.